Stony the road : Reconstruction, white supremacy, and the rise of Jim Crow - Gates, Henry Louis, Jr (Penguin Press, 2019)
The abolition of slavery in the aftermath of the Civil War is a familiar story, as is the civil rights revolution that transformed the nation after World War II. But the century in between remains a mystery: if emancipation sparked "a new birth of freedom" in Lincoln's America, why was it necessary to march in Martin Luther King, Jr.'s America? In this new book, Henry Louis Gates, Jr., one of our leading chroniclers of the African-American experience, seeks to answer that question in a history that moves from the Reconstruction Era to the "nadir" of the African-American experience under Jim Crow, through to World War I and the Harlem Renaissance. Through his close reading of the visual culture of this tragic era, Gates reveals the many faces of Jim Crow and how, together, they reinforced a stark color line between white and black Americans. Bringing a lifetime of wisdom to bear as a scholar, filmmaker, and public intellectual, Gates uncovers the roots of structural racism in our own time, while showing how African Americans after slavery combatted it by articulating a vision of a "New Negro" to force the nation to recognize their humanity and unique contributions to America as it hurtled toward the modern age.